Blending Gelators to Tune Gel Structure and Probe Anion‐Induced Disassembly. Issue 1 (2nd December 2013) - Foster, Jonathan A.; Edkins, Robert M.; Cameron, Gary J.; Colgin, Neil; Fucke, Katharina; Ridgeway, Sam; Crawford, Andrew G.; Marder, Todd B.; Beeby, Andrew; Cobb, Steven L.; Steed, Jonathan W.
Abstract Blending different low molecular weight gelators (LMWGs) provides a convenient route to tune the properties of a gel and incorporate functionalities such as fluorescence. Blending a series of gelators having a common bis‐urea motif, and functionalised with different amino acid‐derived end‐groups and differing length alkylene spacers is reported. Fluorescent gelators incorporating 1‐ and 2‐pyrenyl moieties provide a probe of the mixed systems alongside structural and morphological data from powder diffraction and electron microscopy. Characterisation of the individual gelators reveals that although the expected α‐urea tape motif is preserved, there is considerable variation in the gelation properties, molecular packing, fibre morphology and rheological behaviour. Mixing of the gelators revealed examples in which: 1) the gels formed separate, orthogonal networks maintaining their own packing and morphology, 2) the gels blended together into a single network, either adopting the packing and morphology of one gelator, or 3) a new structure not seen for either of the gelators individually was created. The strong binding of the urea functionalities to anions was exploited as a means of breaking down the gel structure, and the use of fluorescent gel blends provides new insights into anion‐mediated gel dissolution.